Theta-Burst Stimulation for Auditory-Verbal Hallucination in Very-Late-Onset Schizophrenia-Like Psychosis—A Functional Magnetic Resonance Imaging Case Study - Zöllner, Rebecca; Hübener, Anne-Friederike; Dannlowski, Udo; Kircher, Tilo; Sommer, Jens; Zavorotnyy, Maxim (Frontiers in Psychiatry, 2020)
Treating very-late-onset (>60 years) schizophrenia-like psychosis (VLOSLP) is challenging. Age-related factors in elderly individuals (e.g., metabolism, medication side effects, drug-interaction, somatic morbidity) may adversely affect treatment. Novel therapeutic approaches are needed to ensure the favorable therapeutic outcome in geriatric patients. Previously, theta-burst stimulation (TBS), a novel modification of repetitive transcranial magnetic stimulation, was reported being beneficial in the treatment for auditory-verbal hallucination (AVH) in young and middle-aged schizophrenia (SZ) patients. Here we present a case of a male patient aged 73. His first psychotic episode manifested with paranoid delusions, auditory-verbal and tactile hallucinations at the age of 66 and first remitted following a second-generation antipsychotics (SGA). Years later, after a relapse the AVH did not respond to previously effective olanzapine, whereas its augmentation with an inhibitory TBS over the left temporal lobe led to a stable remission. During his second relapse, TBS was again capable of facilitating therapeutic action of SGA in the same patient. Extending to our clinical observation, a series of functional MRI scans employing a tonal activation paradigm depicted altered auditory processing during AVH as well as brain activation change during remission. The current case might indicate to favorable effects of combining conventional medicament therapy and non-invasive brain stimulation techniques for elderly patients. Despite obviously distinct etiologies, the present functional imaging and clinical observation may also demonstrate a possible common pathophysiological pathway underlying AVH in VLOSLP and SZ.